HUBUNGAN AIR SUSU IBU EKSKLUSIF DENGAN JUMLAH GIGI SUSU BAYI USIA 6-12 BULAN DI WILAYAH KERJA PUSKESMAS BOTANIA KOTA BATAM - Ibrahim; Sarita Miguna; Nadya Hanifa (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2024)
Background: The incidence of delayed growth and development of bones and teeth, as well as abnormalities in bone and teeth among the Indonesian population, is quite high. The growth of baby teeth provides an indication of infant nutrition, as sufficient nutrition influences the acceleration of baby teeth growth. Thus, essential nutrients for overall metabolism, foods with high-quality protein and calcium concentration, have a linear relationship with the growth and development of bones and teeth. Methods: : The study employed an analytical observational research design with a cross-sectional approach. The population consisted of 486 infants aged 6-12 months from the Botania Community Health Center. Sample selection utilized Simple Random Sampling with a minimum total sample of 78. Data were analyzed using the Chi-Square Test. Results: There was a significant relationship between Exclusive Breastfeeding and the Number of Baby Teeth Aged 6-12 Months at the Botania Community Health Center, with a obtained p-value of 0.024 < 0.05. Conclusion: Based on the research findings, it is concluded that there is a significant relationship between the Number of Baby Teeth Aged 6-12 Months in the working area of Botania Community Health Center, Batam City, in 2023, with a p-value of 0.024. Keywords: Exclusive Breastfeeding, Infants aged 6-12 months, Baby Teeth